2020
DOI: 10.3390/ani10020212
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Grazing Herbage Mass Affects Grazing Behavior, Herbage Disappearance, and the Residual Nutritive Value of a Pasture during the First Grazing Session

Abstract: During the first hours after the allocation of a grazing strip (first grazing session, GS), dairy cows eat most of the daily dry matter (DM) available. There are few studies that analyze how the grazing-down process changes the characteristics of the pasture during the first GS. The objective of this study was to evaluate the effect of two pre-grazing herbage masses (HM; medium herbage mass (MHM) and high herbage mass (HHM) on the DM disappearance, grazing behavior of dairy cows, and the residual nutritive val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
(67 reference statements)
1
3
0
1
Order By: Relevance
“…The significantly lower CP concentration for PGHM-2500 compared to PGHM-1500, coupled with the similar DMI between PGHM, implies lower nitrogen excretion for PGHM-2500 (Owens et al, 2008;O'Connor et al, 2019), which is important in terms of reducing nitrogen loss in beef production systems. Although, daily DMI did not differ between PGHM treatments due to the similar bite mass and bite rate, it is noteworthy that PGHM-2500, and particularly 2500-6, had a greater DMI during the first 24 h (indicated by greater grazing bites, bite rate and grazing bout duration) which is consistent with previous observations (Piña et al, 2020), and a lower DMI in the second 24 h (indicated by a lower grazing time, number of grazing bites and bite rate) compared to PGHM-1500. The lower DMI for PGHM-2500 in the second 24 h can be due to the greater bite force required due to the greater ADF concentration in the lower layers of the grazing horizon (Tharmaraj et al, 2003) and reduced bite rate as steers try to avoid stem and select leaves (Amaral et al, 2013).…”
Section: Effect Of Pre-grazing Herbage Mass On Steer Performancesupporting
confidence: 91%
“…The significantly lower CP concentration for PGHM-2500 compared to PGHM-1500, coupled with the similar DMI between PGHM, implies lower nitrogen excretion for PGHM-2500 (Owens et al, 2008;O'Connor et al, 2019), which is important in terms of reducing nitrogen loss in beef production systems. Although, daily DMI did not differ between PGHM treatments due to the similar bite mass and bite rate, it is noteworthy that PGHM-2500, and particularly 2500-6, had a greater DMI during the first 24 h (indicated by greater grazing bites, bite rate and grazing bout duration) which is consistent with previous observations (Piña et al, 2020), and a lower DMI in the second 24 h (indicated by a lower grazing time, number of grazing bites and bite rate) compared to PGHM-1500. The lower DMI for PGHM-2500 in the second 24 h can be due to the greater bite force required due to the greater ADF concentration in the lower layers of the grazing horizon (Tharmaraj et al, 2003) and reduced bite rate as steers try to avoid stem and select leaves (Amaral et al, 2013).…”
Section: Effect Of Pre-grazing Herbage Mass On Steer Performancesupporting
confidence: 91%
“…El pastoreo en franjas se asocia con situaciones de rápido agotamiento del recurso forrajero y cuando los niveles de reducción de altura de pradera en dicha situación no se controlan, el CF puede ser afectado de manera negativa (44) . Sin embargo, en situaciones de gestión diferente, en las que las praderas no presentan cambios en su condición durante el día, la TC es constante y el comportamiento del consumo es similar a través del día (29) .…”
Section: La Reducción De La Altura De La Pradera En El Consumounclassified
“…Consequently, it might be possible to estimate herbage intake more precisely based on the number and mass of prehension bites. Several factors, like the animal's anatomy (including mouth and body size), as well as sward factors (such as height and bulk density) have been mentioned to influence bite mass (Rook, 2000) and even duration on pasture (Piña et al, 2020). Furthermore, bite mass is higher within the first 60 min on pasture compared to afterward (Alvarez-Hess et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, DMI estimation is based on the total number of eating chews and the corresponding bite mass. However, as bite mass on pasture shows large variation (0.28 up to 0.96 g of DM/bite) (Piña et al, 2020) and only prehension bites serve for herbage intake, it may be important to differentiate between prehension bites and mastication chews performed during eating. Several sensing devices have recently been developed for automatic recording of behavioural characteristics.…”
Section: Introductionmentioning
confidence: 99%